Live Interface for Generative Rhythm Sequencing - Nuno Diogo Vaz Loureiro de Oliveira (2018)
Traditional rhythmic sequencing techniques are often not ideal to program complex evolving patterns as they offer only linear control to the player. Techniques available to generate variations of a programmed rhythm usually rely on simple randomness or complex programming actions that do not favor the sequencer as a live playing instrument from the musician's perspective. With this in mind, our idea was to create an interactive system able to generate rhythmically informed variations of a pattern previously entered by the user in a direct and familiar real time performative manner, by means of meaningful generative descriptors providing nuanced control over the complex rhythmic sequencing. To this end, Rhythmicator, a Max/MSP application that automatically generates rhythms in real time in a given meter was used to tackle the generative process around the sequence written by the user. The development of the system is based on the Pure Data programming environment, having some parts of Rhythmicator's Max/MSP code been translated and used for this project. A MIDI controller is used to interact with the system's Pure Data patch and MIDI triggers are sent to any MIDI-able device intended. Keywords: generative rhythm, performative sequencing, real time, rhythmicator, pure data, stochastic model, barlow, metric indispensability, physical control